Deep Learning from Scratch : Building with Python from First Principles - Seth Weidman (O'Reilly Media, 2024)
Extremely clear and thorough mental modelsÃ¢??accompanied by working code examples and mathematical explanationsÃ¢??for understanding neural networks Methods for implementing multilayer neural networks from scratch, using an easy-to-understand object-oriented framework Working implementations and clear-cut explanations of convolutional and recurrent neural networks Implementation of these neural network concepts using the popular PyTorch framework